Impacts of Land Cover Changes on Land Surface Temperature Using Landsat Imagery with the Supervised Classification Method - Khairunisa, Farisya Isnaayu; Maulidina, Kintan; Damayanti, Astrid (Graduate School of Universitas Syiah Kuala, 2023)
Land cover changes affecting the area's ecology align with the development and increase in urbanization. Tarogong Kidul Subdistrict, Garut Regency, experienced changes in the land cover which changed the soil surface temperature. This study aims to determine the relationship between changes in land cover and land surface temperature. This study used Landsat 8 Surface Reflectance Tier 1 satellite imagery to extract information on the Normalized Difference Vegetation Index and process ground surface temperatures for three periods, 2014, 2017, and 2020, and the guided classification method. Image collection and processing were carried out using Google Earth Engine and software. ArcGIS Pro. The distribution of land surface temperature was then correlated with changes in the NDVI (value of the land cover vegetation index) using simple linear regression analysis and spatial correlation. This study reveals that land cover change is closely related to an increase in soil surface temperature, as indicated by the rise in soil surface temperature in areas experiencing land use change. The results of the linear regression analysis (84.49%) showed that changes in land cover and the greenness index of vegetation were the most critical driving factors for changes in soil surface temperature.